2000
DOI: 10.1046/j.1365-2141.2000.01869.x
|View full text |Cite
|
Sign up to set email alerts
|

CD34+/CD105+ cells are enriched in primitive circulating progenitors residing in the G0 phase of the cell cycle and contain all bone marrow and cord blood CD34+/CD38low/− precursors

Abstract: Summary. A subset of circulating CD34 cells was found to express CD105 antigen. Sorting experiments showed that most granulocyte±macrophage colony-forming units (GM-CFU) and burst-forming units ± erythroid (BFU-E) were retained in the CD34/CD105À fraction, whereas rare GM-CFU/BFU-E were generated from CD34/CD105 cells. Megakaryocytic aggregates were entirely retained in the CD34/CD105 fraction. Neutralizing doses of an anti-TGF-b1 antibody demonstrated CD34/CD105 cells capable of colony-forming activity withou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
36
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 39 publications
0
36
0
Order By: Relevance
“…56,58,59 For example, TGF-␤1 was shown to inhibit the expression of stem cell factor and its receptor CD117 (c-kit) 60 and was also shown to be a major regulator of erythropoiesis, inhibiting early stages but stimulating later stages. 58 Interestingly, Pierelli et al 40 reported that CD105 is expressed on primitive HSCs and suggested that autocrine TGF-␤1 helps to maintain the resting state and self-renewal capacity of these cells. Other members of the TGF-␤ superfamily, such as activin-A, BMP-2, BMP-4, and BMP-7, have also been implicated as important regulators of mesodermal specification to the hematopoietic fate, or of early hematopoietic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…56,58,59 For example, TGF-␤1 was shown to inhibit the expression of stem cell factor and its receptor CD117 (c-kit) 60 and was also shown to be a major regulator of erythropoiesis, inhibiting early stages but stimulating later stages. 58 Interestingly, Pierelli et al 40 reported that CD105 is expressed on primitive HSCs and suggested that autocrine TGF-␤1 helps to maintain the resting state and self-renewal capacity of these cells. Other members of the TGF-␤ superfamily, such as activin-A, BMP-2, BMP-4, and BMP-7, have also been implicated as important regulators of mesodermal specification to the hematopoietic fate, or of early hematopoietic differentiation.…”
Section: Discussionmentioning
confidence: 99%
“…Endoglin is differentially expressed on hematopoietic cells and was recently recognized as a marker identifying functional long-term repopulating stem cells. 60,61 The potential relevance of endoglin in hematopoiesis can be insinuated from its expression on various human hematopoietic populations, including early Bcell progenitors and erythroblasts in fetal BM, 62 pro-erythroblasts in adult BM, 62,63 CD34+ CB cells, 64 macrophages, 65 and CD4+ T-cells. 66 Additionally, studies assessing hematopoietic differentiation of murine embryonic stem cells (ESC) in vitro have shown that deletion of endoglin results in profound reduction in the formation of hemangioblasts (Fig.…”
Section: 55mentioning
confidence: 99%
“…We have reported an important function for endoglin in cell fate specification and early hematopoiesis, [11][12][13][14][15] and a potential role beyond the embryonic stage is suggested by the expression of this receptor on the hematopoietic stem cell (HSC) isolated from every hematopoietic site, including the aorta-gonad-mesonephros, 16,17 the fetal liver, 18 and the bone marrow (BM), 19,20 in which endoglin has been reported to identify the long-term repopulating HSC. 18,19,21,22 Transcriptional profiling data of proliferating and quiescent HSCs has demonstrated endoglin to be one of the genes selectively expressed in the quiescent HSC subset. 23 Based on this evidence pointing to endoglin as a potential regulator of HSC self-renewal, we hypothesized that deregulated expression of this receptor could be associated with hematopoietic malignancies, in particular acute leukemias.…”
Section: Introductionmentioning
confidence: 99%